Information access by Urban Social Workers in Kenya: A Case of Nakuru City - Kiilu, Peris W.; Kiilu, Vincent Bob (Scientific & Academic Publishing, 2015)
The study was set to identify how Urban Social Workers in Kenya accessed information and how they used it. The objectives of the study were to determine accessibility to information by Urban Social Workers; find out the challenges they experienced in accessing information; and propose solutions to the same. The study found that Social Workers have been for long perceived as non formal information users, but today there is a growing inclination towards use of information from print and electronic media particularly among community based Social Workers, without necessarily impacting on their dependence on oral communication. The paper recommends that the government take greater responsibility in ensuring that Social Workers have access to relevant data and information through disseminating it to the County Information Documentation Centres. The researchers also propose collaboration with information providers drawn from both the electronic and print media. Keywords: Information Access by Urban Social Workers, Information Use by Urban Social Workers, Information Access by Social Workers, Information Needs of Social Workers, Information Use by Social Workers